2021
DOI: 10.1097/acm.0000000000004011
|View full text |Cite
|
Sign up to set email alerts
|

Women on the Frontline: A Changed Workforce and the Fight Against COVID-19

Abstract: COVID-19 is a worldwide pandemic, with frontlines that look drastically different than in past conflicts: that is, women now make up a sizeable majority of the health care workforce. American women have a long history of helping in times of hardship, filling positions on the home front vacated by men who enlisted as soldiers during World War I and similarly serving in crucial roles on U.S. military bases, on farms, and in factories during World War II. The COVID-19 pandemic has represented a novel battleground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 9 publications
3
22
0
Order By: Relevance
“…This study explored HCWs' perceptions and beliefs of vaccine effectiveness and advocacy in relation to the emerging SARS-CoV-2 Omicron variant in KSA. Most respondents were females (62%), similar to a previous study about the Delta variants concern in KSA, and in agreement with other studies showing females to be the mainstream among HCWs [11,13,14].…”
Section: Discussionsupporting
confidence: 91%
“…This study explored HCWs' perceptions and beliefs of vaccine effectiveness and advocacy in relation to the emerging SARS-CoV-2 Omicron variant in KSA. Most respondents were females (62%), similar to a previous study about the Delta variants concern in KSA, and in agreement with other studies showing females to be the mainstream among HCWs [11,13,14].…”
Section: Discussionsupporting
confidence: 91%
“…Although the Saudi MOH recently announced that the Delta variant is circulating in the KSA after these data were collected, many HCWs anticipated that this variant would be encountered. While most of our study respondents (62.2%) were female, this is in line with other studies that showed a predominance of the female sex among frontline COVID-19 HCWs [15,20]. Among the estimated 49 million frontline HCWs in the E.U., around 76% are female [21].…”
Section: Discussionsupporting
confidence: 90%
“…Rabinowitz and Rabinowitz, 25 Lewiss and Jagsi, 26 20 speak about the importance of diversity within Hispanic identity, noting that "academic medicine risks ignoring the distinctive struggles of different minority groups if antiracism efforts are solely aimed at racial categories or an amalgamate 'people of color. '" "A more inclusive future for academic medicine, " as noted by members of our journal's editorial board, 16 "will be enacted not through sentiment, but by means of individual, structural, and symbolic action. "…”
Section: Advancing Equity In Academic Medicinementioning
confidence: 99%